Strategi Promosi Melalui Instagram @tanjongtinggi_official Dalam Meningkatkan Minat Wisatawan Pantai Tanjung Tinggi Belitung - Henny Henny; Rachmawati Windyaningrum (Universitas Maritim AMNI Semarang, 2024)
The use of social media, especially Instagram, has become a widely utilized platform for promoting tourist destinations. Instagram @tanjongtinggi_official is one such social media channel used by Tanjung Tinggi Beach for promotion. Through the use of photo and video features on Instagram, it becomes easier to promote Tanjung Tinggi Beach to tourists who are not yet familiar with it. This research aims to explore the promotional planning through the @tanjongtinggi_official account in increasing tourist visits to Tanjung Tinggi Beach in Belitung. The research method employs qualitative research to elucidate the uniqueness of @tanjongtinggi_official on Instagram in promoting its tourism. This study adopts a case study design. Data collection is conducted through observation and interviews, with informant selection using purposive sampling technique. Interviews are conducted with key informants, namely the admin of @tanjongtinggi_official and Instagram users who have visited Tanjung Tinggi Beach. Data analysis utilizes the Interactive Model technique, and validity is ensured through triangulation of data collection techniques including informant interviews, observation, and documentation. The results indicate that the planning carried out by the @tanjongtinggi_official Instagram account utilizes visually appealing content presentation and captions, leverages the following feature on Instagram, relevant hashtag usage, photo postings, reposts, mentions, tagged photos, and active interaction with followers to facilitate the promotion of Tanjung Tinggi Beach to tourists, thereby increasing tourist interest in visiting.